Economia circular aplicada à gestão de ativos no setor de energia: extensão de vida útil e descarte de transformadores de potência - MUNIZ, Robert Belfort (2024)
The circular economy proposes a break with the linear economic model (extract, transform and discard) aiming at the development of materials and products that can circulate efficiently and be reallocated in the production chain without loss of quality, in addition to reuse, recomposition into new materials, and useful life extension, thus generating greater environmental awareness and technological efficiency. Among the sustainable development objectives proposed by the UN, SDG 12 proposes as a global goal that by 2030 societies are resilient, committed, and responsible in the production and consumption of materials, goods and services, with greater environmental responsibility. This proposition requires a paradigm shift in the industrial sectors, in the fight against planned obsolescence, demanding a new economic model in the energy sector, with the use of equipment and materials, designed to achieve circularity in the production process, in an efficient way. Asset management is a methodology that seeks to maximize the generation of value from assets, providing the necessary support for the organization to decide the optimal period for replacing assets at the end of their useful life. The dissertation proposes the analysis of the energy management process, with an emphasis on the analysis and evaluation of the potential for applying the principles of circularity in operational continuity, and in the useful life of power transformers and their environmental impacts in the Brazilian energy sector. This work proposes the analysis of the application of the main principles of circular economy in managing the life cycle of power transformers and aims to evaluate how the use of new tools may impact the extraction and use of resources from the environment, and how can the production and generation of solid waste be reduced through the reuse of these materials.